Calidad biológica del agua del río Amojú. Jaén, Cajamarca. 2013 - Polo Corro, José Luis (2014)
In June, 2013, there was carried out the biological characterization of 6 stations of sampling, distributed in the course the CuencaAmojú, located in Jaen in the north of Peru, in the Region Cajamarca, from the 549 - 1236 msnm; biological parameters were analyzed across the identification of the macroinvertebrates bentónicos in situ, this waylike ex-situ.Identified 28 families of macroinvertebrates, being established that the water quality of the basin of the river Amojú, based in in the Biotic Index for the rivers of the north of the north of Peru nPeBMWP; it was ofAcceptable quality for three stations of sampling (E-1, E-2 and E-6), whereasintheremainingones(E-3, E-4and E-5) thequalitychangesfrom Regulatingto Bad. This basin is being altered due to the activities of deforestation and agriculture, this way like to the bad disposition of the aguas served as the populated centers.